Animating Brains. Issue 3 (13th June 2016) - Borck, Cornelius
Abstract : A recent paper famously accused the rising field of social neuroscience of using faulty statistics under the catchy title 'Voodoo Correlations in Social Neuroscience'. This Special Issue invites us to take this claim as the starting point for a cross-cultural analysis: in which meaningful ways can recent research in the burgeoning field of functional imaging be described as, contrasted with, or simply compared to animistic practices? And what light does such a reading shed on the dynamics and effectiveness of a century of brain research into higher mental functions? Reviewing the heated debate from 2009 around recent trends in neuroimaging as a possible candidate for current instances of 'soul catching', the paper will then compare these forms of primarily image-based brain research with older regimes, revolving around the deciphering of the brain's electrical activity. How has the move from a decoding paradigm to a representational regime affected the conceptualisation of self, psyche, mind and soul (if there still is such an entity)? And in what ways does modern technoscience provide new tools for animating brains?